2019
DOI: 10.1158/1538-7445.am2019-5156
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5156: In vitro application of tumor-treating fields to suppress tunneling nanotubes in mesothelioma

Abstract: The purpose of this study was to evaluate the effects of tumor-treating fields (TTFields) on tunneling nanotubes (TNTs) in malignant mesothelioma. TTFields have emerged as a therapeutic modality for the treatment of glioblastoma, through application of alternating electric fields, which exert dipole alignment and dielectrophoretic force. The dielectrophoretic force is intensified in cellular compartments that are non-uniform in size and shape such as the mitotic furrow. TNTs are filamentous actin protrusions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…TNTs are protrusions in actin-containing membranes that are formed in excess in many pathological conditions; for instance, malignant pleural mesothelioma is rich in TNTs. The application of dielectrophoretic force inhibited TNTs formation in mesothelioma by 60% over 72 h and made these cells sensitized to the cytotoxic effect of conventional chemotherapy [152,153]. Other studies have confirmed that TNTs are upregulated in many invasive cancer cells, and their further formation is a response to hypoxic conditions or chemotherapeutic drugs.…”
Section: Tunnel Nanotubesmentioning
confidence: 95%
“…TNTs are protrusions in actin-containing membranes that are formed in excess in many pathological conditions; for instance, malignant pleural mesothelioma is rich in TNTs. The application of dielectrophoretic force inhibited TNTs formation in mesothelioma by 60% over 72 h and made these cells sensitized to the cytotoxic effect of conventional chemotherapy [152,153]. Other studies have confirmed that TNTs are upregulated in many invasive cancer cells, and their further formation is a response to hypoxic conditions or chemotherapeutic drugs.…”
Section: Tunnel Nanotubesmentioning
confidence: 95%